Governance and risk in emerging and global markets - Motamen-Samadian, Sima (Basingstoke [England] ; New York : Palgrave Macmillan, 2005)
This book provides an interesting combination of papers, each related to governance at different levels. Governance is assessed from the regulatory point of view, and from the market's point of view. The question is how different factors such as international regulations, domestic deregulation, choice of production method, use of a specific risk-detecting method, and a new market environment, can affect governance and the levels of risk faced by investors and stakeholders. The book also includes studies that correspond to risk reduction and management in different sectors such as bank, telecommunications, retail, utilities and agriculture, as well as financial markets in different parts of the world in both emerging and establish markets. Finally, the book offers interesting and informative studies relating to Iraq and its stock market, and also looks at possible methods of fund-raising.
Ch. 1. Introduction / Sima Motamen-Samadian -- Ch. 2. Basel II: Principles of Avoiding Regulatory Failure / Joseph Tanega -- Ch. 3. Developing and Understanding of Credit-Risk processes in Selected UK Sectors / Ann Puri and Harry Thapar -- Ch. 4. Risk Analysis and Sustainability of Alternative Crop Production Systems / Maqsood Hussain and Abdul Saboor -- Ch.5. Country Risk and Governance: Strange Bedfellows? / Michel Henry Bouchet and Bertrand Groslambert -- Ch. 6. Market Deregulations, Volatility and Spillover Effects: Experience from Emerging Stockmarkets / Duc Khuong Nguyen -- Ch. 7. The Baghdad Stock Exchange: A Dismal First Decade ... A Growth Path Ahead? / Kadom J.A. Shubber and Talal A. Kadhim -- Ch. 8. Risk Management and Securitization of Assets: The case of Iraq / Ola Sholarin.
Includes bibliographical references and index.
Keywords: Investments -- Developing countries; Securities -- Developing countries; Credit -- Developing countries; Risk management -- Developing countries; Developing countries -- Economic policy